Cylinder block casting and preparation method thereof

By adjusting the chemical composition of the air compressor cylinder block to form a high pearlite matrix structure, the problems of the existing cylinder block's tensile resistance, hardness and pore defect rate are solved, and higher performance and a wider application range are achieved.

CN119685693APending Publication Date: 2025-03-25GREE (WUAN) PRECISION EQUIP MFG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411732784.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Due to the limitations of materials, the existing air compressor cylinder blocks have problems such as tensile resistance, poor hardness and high pore defect rate, which is difficult to meet users' needs for improving quality.

Method used

By adjusting the chemical composition of the cylinder block casting, the carbon content is 3.2% to 3.45%, silicon element 1.7% to 1.9%, manganese element 0.85% to 0.9%, etc., a high pearlite matrix structure is formed to improve tensile resistance and hardness.

Benefits of technology

It significantly improves the tensile resistance and hardness of the cylinder block, reduces the pore defect rate, enhances the wear resistance and corrosion resistance of the material, thereby expanding the application range and service life of the cylinder block.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685693A_ABST
    Figure CN119685693A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of commercial vehicle air compressor air cylinder bodies, in particular to an air cylinder body casting and a preparation method thereof.The air cylinder body casting comprises, by weight, 3.2%-3.45% of carbon element, 1.7%-1.9% of silicon element, 0.85%-0.9% of manganese element, 0.06%-0.08% of phosphorus element, 0.06%-0.09% of sulfur element, 0.45%-0.54% of copper element, 0.12%-0.20% of chromium element, 0.026%-0.040% of antimony element, 0.053%-0.061% of tin element and the balance iron element. The cylinder block casting has the advantages of high tensile strength and hardness, and the application range of the cylinder is effectively widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cylinders, and in particular to a cylinder body casting and a preparation method thereof. Background Art

[0002] The cylinder block of a commercial vehicle air compressor is the source of compressed air. Its performance not only affects the normal operation of the engine but also affects the braking performance and fuel economy. It is one of the key core components of commercial vehicles.

[0003] The cylinder block of commercial vehicle air compressor is currently mainly made of gray cast iron, which is widely used because of its flake graphite's characteristics of shock absorption, lubrication, pressure resistance and wear resistance. With the intensified competition in the market environment and the increasing demand for quality from users, higher requirements are placed on the performance of cylinder block castings. Excellent performance can not only bring users a good user experience, but also enhance market competitiveness and create huge economic value. However, due to the limitations of the material, the current air compressor cylinder block still has problems with poor tensile strength, poor hardness and high porosity rate. Summary of the invention

[0004] The object of the present invention is to avoid the deficiencies in the prior art and provide a cylinder block casting, which has the advantages of higher tensile strength and hardness, and effectively improves the applicable scope of the cylinder.

[0005] To achieve one of the above purposes, the present invention provides the following technical solutions:

[0006] A cylinder block casting is provided, the cylinder block casting comprising the following elements in weight percentage:

[0007] Carbon 3.2%~3.45%

[0008] Silicon 1.7%~1.9%

[0009] Manganese 0.85%~0.9%

[0010] Phosphorus 0.06%~0.08%

[0011] Sulfur 0.06%~0.09%

[0012] Copper 0.45%~0.54%

[0013] Chromium 0.12%~0.20%

[0014] Antimony 0.026%~0.040%

[0015] Tin element 0.053%~0.061%.

[0016] In some embodiments, when the cylinder block casting is single-cylinder water-cooled, the percentages of the elements are as follows: carbon 3.2% to 3.45%

[0017] Silicon 1.7%~1.9%

[0018] Manganese 0.85%~0.9%

[0019] Phosphorus 0.06%~0.08%

[0020] Sulfur 0.06%~0.09%

[0021] Copper 0.45%~0.50%

[0022] Chromium 0.17%~0.2%

[0023] Antimony 0.032%~0.036%

[0024] Tin element 0.053%~0.058%.

[0025] In some embodiments, when the cylinder block casting is a double-cylinder water-cooled one, the percentage of each element is as follows:

[0026] Carbon 3.2%~3.45%

[0027] Silicon 1.7%~1.9%

[0028] Manganese 0.85%~0.9%

[0029] Phosphorus 0.06%~0.08%

[0030] Sulfur 0.06%~0.09%

[0031] Copper 0.50%~0.54%

[0032] Chromium 0.17%~0.2%

[0033] Antimony element 0.036%~0.040%

[0034] Tin element 0.055%~0.061%.

[0035] In some embodiments, when the cylinder block casting is single-cylinder or double-cylinder air-cooled, the percentage of each element is as follows:

[0036] Carbon 3.2%~3.45%

[0037] Silicon 1.7%~1.9%

[0038] Manganese 0.85%~0.9%

[0039] Phosphorus 0.06%~0.08%

[0040] Sulfur 0.06%~0.09%

[0041] Copper 0.43%~0.48%

[0042] Chromium 0~0.12%

[0043] Antimony 0.026%~0.031%

[0044] Tin element 0.053%~0.058%.

[0045] In some embodiments, the cylinder block casting has a pearlite content greater than 98%.

[0046] The casting matrix is ​​mainly composed of fine flake pearlite, the pearlite content is greater than 98%, the casting cylinder piston hardness is 200-240HBW, and the tensile strength is greater than 250Mpa, thereby obtaining excellent wear resistance performance.

[0047] Also provided is a method for preparing the above-mentioned cylinder body casting, comprising the following steps:

[0048] First, pig iron, steel and recycled materials are put into a furnace to heat and melt. The composition of the molten iron is measured and then the amount of carbon, silicon, manganese, phosphorus, sulfur, copper, chromium, antimony and tin related alloys added is calculated according to the formula. The alloy is put into the furnace for smelting, poured and solidified to obtain a casting.

[0049] The prepared pig iron, steel and recycled materials are put into the furnace for heating and melting. This step requires controlling the temperature of the furnace and the melting time to ensure that the raw materials can be fully melted. In the molten iron, alloys of carbon, silicon, manganese, phosphorus, sulfur, copper, chromium, antimony, tin and other elements are added according to the formula. These alloys are added to adjust the chemical composition of the molten iron to achieve the performance requirements required for the cylinder casting.

[0050] In some embodiments, when the temperature of the molten iron is greater than 1400° C., the molten iron composition is sampled and analyzed.

[0051] When the temperature of the molten iron reaches more than 1400℃, sampling and analysis are carried out to ensure that the composition of the molten iron meets the predetermined standards. This step is the key to quality control and ensures that the chemical composition of the material is within a controllable range.

[0052] In some embodiments, before being taken out of the furnace, the temperature of the cylinder material is measured and then taken out of the furnace until it meets the requirements.

[0053] Before the molten iron comes out of the furnace, the temperature of the cylinder material needs to be measured again to ensure that it meets the requirements for coming out of the furnace. This step is to ensure that the material will not degrade in performance due to improper temperature during subsequent casting or processing.

[0054] In some embodiments, after weighing each element alloy, the weight of each alloy needs to be confirmed again.

[0055] After weighing each element alloy, it is necessary to reconfirm the weight of each alloy to ensure that the correct amount of alloy has been added. This step is crucial to ensure the accuracy and consistency of the material composition.

[0056] Also provided is a cylinder for an automobile air compressor, which is made from the above-mentioned cylinder body casting.

[0057] The beneficial effects of a cylinder casting of the present invention are as follows:

[0058] (1) The cylinder casting of the present invention has a carbon content of 3.2% to 3.45%. During the solidification process of the molten iron, a portion of the free carbon of the carbon element forms a graphite matrix. The graphite has a certain lubricating effect. The gray cast iron graphite is mainly in the form of flaky A-type graphite. The present invention adopts a higher carbon content range. On the one hand, it can ensure that more graphite is precipitated from the casting under good incubation conditions during the solidification process of the casting, ensuring that the casting is dense and leak-free. On the other hand, the high carbon content of the body liquid changes the surface tension of the molten iron and reduces the occurrence of invasive pores.

[0059] (2) The cylinder block casting of the present invention, wherein the silicon content is 1.7%-1.9%, silicon can improve the corrosion resistance of the casting, reduce oxidation and corrosion in the environment, improve thermal fatigue performance in a high temperature environment, and increase the thermal conductivity of cast iron. Usually, the silicon content should be reduced under high carbon content components to ensure that the molten iron solidifies near the eutectic point. The present invention does not reduce silicon on the basis of high carbon content to improve the corrosion resistance of the casting.

[0060] (3) The cylinder casting of the present invention has a manganese content of 0.85-0.9% and a sulfur content of 0.06-0.09%. On the one hand, the manganese and sulfur elements combine to form heterogeneous nuclei, and on the other hand, they can promote the formation of pearlite. The manganese and sulfur ranges of the present invention ensure the nucleation conditions, and also prevent the formation of harmful matrices such as FeS due to high sulfur content.

[0061] (4) The cylinder block casting of the present invention has a phosphorus content of 0.06-0.08%. The present invention adopts a low-phosphorus solution and has no phosphorus eutectic hard phase. Different from other materials, phosphorus eutectic easily forms "Widmanstätten structure" and leads to reduced mechanical properties.

[0062] (5) In the cylinder block casting of the present invention, the three elements of copper, antimony and tin can promote the formation of pearlite to varying degrees. The combination of the three phases can achieve a higher effect than the sum of the quantities, forming a high pearlite matrix structure on the basis of high carbon, thereby achieving a tensile strength greater than 250 MPa and a hardness of 200 to 240 HBW.

[0063] (6) The cylinder block casting of the present invention has a chromium content of 0.17-0.2%. The present invention increases the wear resistance of the casting by adding chromium and carbon to form a combined carbide hard phase.

[0064] (7) The cylinder block casting of the invention, wherein the deviation of the alloy copper, antimony and tin is adjusted according to the difference in solidification state of the different product structures.

[0065] (8) The cylinder block casting of the invention has the advantages of high tensile strength and hardness, which effectively improves the application range of the cylinder. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 It is a rendering of an automobile air compressor cylinder made from a cylinder body casting according to an experimental example of the present invention.

[0067] Figure 2 It is a rendering of the second automobile air compressor cylinder made from the cylinder body casting of the experimental example of the present invention.

[0068] Figure 3 It is a rendering of the third automobile air compressor cylinder made from the cylinder body casting of the experimental example of the present invention.

[0069] Figure 4 It is a rendering of the fourth automobile air compressor cylinder made from the cylinder body casting of the experimental example of the present invention. DETAILED DESCRIPTION

[0070] The preferred embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the preferred embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0071] The terms used in the present invention are only for the purpose of describing specific implementation regulations, and are not intended to limit the present invention. The singular forms "a", "the" used in the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in this article refers to and includes any or all possible combinations of one or more associated listed items.

[0072] It should be understood that although the terms "first", "second", "third", etc. may be used to describe various information in the present invention, such information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present invention, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0073] Example 1

[0074] The cylinder block of a commercial vehicle air compressor is the source of compressed air. Its performance not only affects the normal operation of the engine but also affects the braking performance and fuel economy. It is one of the key core components of commercial vehicles.

[0075] The cylinder block of commercial vehicle air compressor is currently mainly made of gray cast iron, which is widely used because of its flake graphite's characteristics of shock absorption, lubrication, pressure resistance and wear resistance. With the intensified competition in the market environment and the increasing demand for quality from users, higher requirements are placed on the performance of cylinder block castings. Excellent performance can not only bring users a good user experience, but also enhance market competitiveness and create huge economic value. However, due to the limitations of the material, the current air compressor cylinder block still has problems with poor tensile strength, poor hardness and high porosity rate.

[0076] In view of the above technical problems, the present embodiment discloses a cylinder block casting, which includes the following elements in weight percentage: 3.2% to 3.45% carbon, 1.7% to 1.9% silicon, 0.85% to 0.9% manganese, 0.06% to 0.08% phosphorus, 0.06% to 0.09% sulfur, 0.45% to 0.54% copper, 0.12% to 0.20% chromium, 0.026% to 0.040% antimony, and 0.053% to 0.061% tin.

[0077] The cylinder block casting is made of grey cast iron in the cast state, which is scientifically blended with the five conventional elements of carbon, silicon, manganese, phosphorus and sulfur, and a certain amount of alloying elements such as copper, chromium, antimony and tin are added.

[0078] Carbon: 3.2%-3.45%% Carbon element forms a graphite matrix as part of the free carbon during the solidification of molten iron. Graphite has a certain lubricating effect. The gray cast iron graphite is mainly in the form of flake A-type graphite. The present invention adopts a higher carbon content range. On the one hand, it can ensure that more graphite is precipitated from the casting under good inoculation conditions during the solidification of the casting, ensuring that the casting is dense and leak-free. On the other hand, the high carbon content of the body liquid changes the surface tension of the molten iron and reduces the occurrence of invasive pores.

[0079] Silicon: 1.7% to 1.9% Silicon can improve the corrosion resistance of castings, reduce oxidation and corrosion in the environment, improve thermal fatigue performance in high temperature environments, and increase the thermal conductivity of cast iron. Usually, the silicon content should be reduced under high carbon content components to ensure that the molten iron solidifies near the eutectic point. The present invention does not reduce silicon on the basis of high carbon content to improve the corrosion resistance of castings.

[0080] Manganese: 0.85-0.9% Sulfur: 0.06-0.09%

[0081] On the one hand, manganese and sulfur combine to form heterogeneous nuclei, and on the other hand, they can promote the formation of pearlite. The manganese and sulfur ranges of the present invention ensure the nucleation conditions, and also prevent the formation of harmful matrices such as FeS due to high sulfur.

[0082] Phosphorus: 0.06-0.08% The present invention adopts a low-phosphorus solution and has no phosphorus eutectic hard phase, which is different from other materials. Phosphorus eutectic easily forms "Widmanstätten structure" and leads to reduced mechanical properties.

[0083] Copper, antimony and tin can promote the formation of pearlite to varying degrees, and the combined effect of the three phases can be higher than the sum of the quantities. Figure 3 The alloy elements are superimposed in proportion to form a high pearlite matrix structure on the basis of high carbon, thereby achieving a tensile strength greater than 250MPa and a hardness of 200-240HBW.

[0084] Chromium: 0.17-0.2% The present invention increases the wear resistance of the casting by adding chromium and carbon to form a compound carbide hard phase.

[0085] Specifically,

[0086] The cylinder block casting of this embodiment optimizes the physical and chemical properties of the material by precisely controlling the content of various elements to meet the needs of specific applications. Carbon content control (3.2-3.45%)

[0087] The high carbon content promotes the precipitation of graphite, thereby improving the density and anti-leakage performance of the casting.

[0088] The amount of carbon added is precisely controlled during the smelting process to ensure that the carbon content in the molten iron is within the specified range.

[0089] Silicon content control (1.7~1.9%)

[0090] Improve the corrosion resistance and thermal fatigue performance of castings at high temperatures, and increase thermal conductivity.

[0091] Adding an appropriate amount of silicon during the smelting process and ensuring that its content is within the specified range can improve the performance of the casting.

[0092] Manganese and sulfur content control (manganese: 0.85 ~ 0.9%, sulfur: 0.06 ~ 0.09%)

[0093] The mechanical properties of the material are improved by forming heterogeneous nucleation and promoting the formation of pearlite.

[0094] The addition of manganese and sulphur is precisely controlled to ensure that their contents are within the specified range to avoid the formation of harmful phases.

[0095] Phosphorus content control (0.06~0.08%)

[0096] A low-phosphorus solution is adopted to avoid the formation of phosphorus eutectic hard phase and improve mechanical properties.

[0097] Strictly control the amount of phosphorus added to ensure that its content is within the specified range to avoid the formation of "Widmanstätten structure".

[0098] Synergistic effects of copper, antimony and tin

[0099] Promotes pearlite formation, improves tensile properties and hardness.

[0100] During the smelting process, appropriate amounts of copper, antimony and tin are added to ensure that their contents can work synergistically to form a high pearlite matrix structure.

[0101] Chromium content control (0.17~0.2%)

[0102] By forming a combined carbide hard phase, the wear resistance of the casting is increased.

[0103] An appropriate amount of chromium is added during the smelting process, ensuring that its content is within the specified range to improve wear resistance.

[0104] Adjustment of alloy elements: deviation adjustment of copper, antimony and tin according to different product structures and solidification states.

[0105] Depending on the specific product requirements and solidification characteristics, the contents of copper, antimony and tin are adjusted to optimize material properties.

[0106] Through the precise control of the above elements, the cylinder body casting has high tensile strength. The material hardness reaches 200-240HBW, which improves the application range and durability of the cylinder.

[0107] Through this precise material design and element control, the cylinder block casting is able to improve wear resistance and corrosion resistance while maintaining high tensile strength and hardness, effectively extending the application range and service life of the cylinder block.

[0108] The pearlite content of the cylinder block material is greater than 98%.

[0109] The casting matrix is ​​mainly composed of fine flake pearlite, the pearlite content is greater than 98%, the casting cylinder piston hardness is 200-240HBW, and the tensile strength is greater than 250Mpa, thereby obtaining excellent wear resistance performance.

[0110] Example 2

[0111] To further illustrate the various types of cylinder materials of the present invention, based on Example 1, when the cylinder block is a single-cylinder water-cooled cylinder,

[0112] Please refer to Table 1,

[0113] Table 1 Element composition of single-cylinder water-cooled cylinder

[0114] The percentages of each element are as follows: carbon 3.2% to 3.45%, silicon 1.7% to 1.9%, manganese 0.85% to 0.9%, phosphorus 0.06% to 0.08%, sulfur 0.06% to 0.09%, copper 0.45% to 0.50%, chromium 0.17% to 0.2%, antimony 0.032% to 0.036%, and tin 0.053% to 0.058%.

[0115] Carbon: 3.2% to 3.45% During the solidification of molten iron, a portion of the free carbon forms a graphite matrix. Graphite has a certain lubricating effect. The gray cast iron graphite is mainly flaky A-type graphite. This embodiment adopts a higher carbon content range. On the one hand, it can ensure that more graphite is precipitated from the casting under good inoculation conditions during the solidification of the casting, ensuring that the casting is dense and leak-free. On the other hand, the high carbon content of the body liquid changes the surface tension of the molten iron and reduces the occurrence of invasive pores.

[0116] Silicon: 1.7-1.9% silicon can improve the corrosion resistance of castings, reduce oxidation and corrosion in the environment, improve thermal fatigue performance in high temperature environments, and increase the thermal conductivity of cast iron. Usually, the silicon content should be reduced under high carbon content components to ensure that the molten iron solidifies near the eutectic point. The present invention does not reduce silicon on the basis of high carbon content to improve the corrosion resistance of castings.

[0117] Manganese: 0.85-0.9% Sulfur: 0.06-0.09%

[0118] On the one hand, manganese and sulfur combine to form heterogeneous nuclei, and on the other hand, they can promote the formation of pearlite. The manganese and sulfur ranges of the present invention ensure the nucleation conditions, and also prevent the formation of harmful matrices such as FeS due to high sulfur.

[0119] Phosphorus: 0.06-0.08% This embodiment adopts a low-phosphorus solution, and has no phosphorus eutectic hard phase, which is different from other materials. Phosphorus eutectic easily forms "Widmanstätten structure" and leads to reduced mechanical properties.

[0120] Copper, antimony and tin can promote the formation of pearlite to varying degrees, and the three phases can be used together to achieve a higher effect than the sum of the numbers. This embodiment uses the above alloy elements to form a high pearlite matrix structure on the basis of high carbon, thereby achieving a tensile strength greater than 250MPa and a hardness of 200-240HBW.

[0121] Chromium: 0.17-0.2% The present invention increases the wear resistance of castings by adding chromium and carbon to form a carbide hard phase in a compound state. Chromium is adjusted according to the difference in solidification state of different product structures.

[0122] Example 3

[0123] To further illustrate the various types of cylinder materials of the present invention, based on Example 1, when the cylinder block is a double-cylinder water-cooled cylinder,

[0124] Please refer to Table 2,

[0125] Table 2 Element composition of double-cylinder water-cooled cylinder

[0126] The percentages of each element are as follows:

[0127] Carbon 3.2%~3.45%, silicon 1.7%~1.9%, manganese 0.85%~0.9%, phosphorus 0.06%~0.08%, sulfur 0.06%~0.09%, copper 0.50%~0.54%, chromium 0.17%~0.2%, antimony 0.036%~0.040%, tin 0.055%~0.061%.

[0128] Carbon: 3.2% to 3.45% During the solidification of molten iron, a portion of the free carbon forms a graphite matrix. Graphite has a certain lubricating effect. The gray cast iron graphite is mainly flaky A-type graphite. This embodiment adopts a higher carbon content range. On the one hand, it can ensure that more graphite is precipitated from the casting under good inoculation conditions during the solidification of the casting, ensuring that the casting is dense and leak-free. On the other hand, the high carbon content of the body liquid changes the surface tension of the molten iron and reduces the occurrence of invasive pores.

[0129] Silicon: 2.1-2.25% silicon can improve the corrosion resistance of castings, reduce oxidation and corrosion in the environment, improve thermal fatigue performance in high temperature environments, and increase the thermal conductivity of cast iron. Usually, the silicon content should be reduced under high carbon content components to ensure that the molten iron solidifies near the eutectic point. The present invention does not reduce silicon on the basis of high carbon content to improve the corrosion resistance of castings.

[0130] Manganese: 0.85-0.9% Sulfur: 0.06-0.09%

[0131] On the one hand, manganese and sulfur combine to form heterogeneous nuclei, and on the other hand, they can promote the formation of pearlite. The manganese and sulfur ranges of the present invention ensure the nucleation conditions, and also prevent the formation of harmful matrices such as FeS due to high sulfur.

[0132] Phosphorus: 0.06-0.08% This embodiment adopts a low-phosphorus solution, and has no phosphorus eutectic hard phase, which is different from other materials. Phosphorus eutectic easily forms "Widmanstätten structure" and leads to reduced mechanical properties.

[0133] Copper, antimony and tin can promote the formation of pearlite to varying degrees, and the three phases can be used together to achieve a higher effect than the sum of the numbers. This embodiment uses the above alloying elements to form a high pearlite matrix structure on the basis of high carbon, thereby achieving a tensile strength greater than 250MPa and a hardness of 200-240HBW.

[0134] Chromium: 0.17-0.2% The present invention increases the wear resistance of castings by adding chromium and carbon to form a carbide hard phase in a compound state. Chromium is adjusted according to the difference in solidification state of different product structures.

[0135] Example 4

[0136] To further illustrate the various types of cylinder materials of the present invention, based on Example 1, when the cylinder block is single-cylinder or double-cylinder air-cooled,

[0137] Please refer to Table 3,

[0138] Table 3 Element composition of single and double cylinder air-cooled cylinders

[0139] The percentages of each element are as follows:

[0140] Carbon 3.2%~3.45%, silicon 1.7%~1.9%, manganese 0.85%~0.9%, phosphorus 0.06%~0.08%, sulfur 0.06%~0.09%, copper 0.43%~0.48%, chromium 0~0.12%, antimony 0.026%~0.031%, tin 0.053%~0.058%.

[0141] Carbon: 3.2% to 3.45% During the solidification of molten iron, a portion of the free carbon forms a graphite matrix. Graphite has a certain lubricating effect. The gray cast iron graphite is mainly flaky A-type graphite. This embodiment adopts a higher carbon content range. On the one hand, it can ensure that more graphite is precipitated from the casting under good inoculation conditions during the solidification of the casting, ensuring that the casting is dense and leak-free. On the other hand, the high carbon content of the body liquid changes the surface tension of the molten iron and reduces the occurrence of invasive pores.

[0142] Silicon: 1.7-1.9% silicon can improve the corrosion resistance of castings, reduce oxidation and corrosion in the environment, improve thermal fatigue performance in high temperature environments, and increase the thermal conductivity of cast iron. Usually, the silicon content should be reduced under high carbon content components to ensure that the molten iron solidifies near the eutectic point. The present invention does not reduce silicon on the basis of high carbon content to improve the corrosion resistance of castings.

[0143] Manganese: 0.85-0.9% Sulfur: 0.06-0.09%

[0144] On the one hand, manganese and sulfur combine to form heterogeneous nuclei, and on the other hand, they can promote the formation of pearlite. The manganese and sulfur ranges of the present invention ensure the nucleation conditions, and also prevent the formation of harmful matrices such as FeS due to high sulfur.

[0145] Phosphorus: 0.06-0.08% This embodiment adopts a low-phosphorus solution, and has no phosphorus eutectic hard phase, which is different from other materials. Phosphorus eutectic easily forms "Widmanstätten structure" and leads to reduced mechanical properties.

[0146] Copper, antimony and tin can promote the formation of pearlite to varying degrees, and the three phases can be used together to achieve a higher effect than the sum of the numbers. This embodiment uses the above alloying elements to form a high pearlite matrix structure on the basis of high carbon, thereby achieving a tensile strength greater than 250MPa and a hardness of 200-240HBW.

[0147] Chromium: 0.17-0.2% The present invention increases the wear resistance of castings by adding chromium and carbon to form a carbide hard phase in a compound state. Chromium is adjusted according to the difference in solidification state of different product structures.

[0148] According to the difference in solidification state of different product structures, chromium deviation adjustment is carried out. Single and double cylinder air-cooled cylinder bodies are mainly air-cooled, and the production casting molten iron solidifies relatively quickly, so the chromium addition is controlled within the range of <0.12%.

[0149] Example 5

[0150] In order to further illustrate the preparation method of the cylinder casting of the present invention, the following contents are disclosed: The preparation method of the cylinder casting comprises the following steps:

[0151] First, pig iron, steel and recycled materials are put into the furnace to heat and melt. The composition of the molten iron is measured, and then the relevant alloys of carbon, silicon, manganese, phosphorus, sulfur, copper, chromium, antimony and tin are calculated according to the formula and put into the furnace for smelting. After pouring and solidification, castings are obtained.

[0152] When the molten iron temperature is greater than 1400°C, samples are taken to analyze the molten iron composition.

[0153] Before taking out of the furnace, measure the temperature of the cylinder material and wait until it meets the requirements before taking out of the furnace.

[0154] After weighing the alloy of each element, the weight of each alloy needs to be confirmed again.

[0155] Specifically, the cylinder block casting preparation method of the present invention is a process flow for accurately controlling the material composition and performance. The following are the specific implementation steps:

[0156] Prepare pig iron, steel and recycled materials, which are the basic raw materials for cylinder block castings.

[0157] The prepared pig iron, steel and recycled materials are put into the furnace for heating and melting. This step requires controlling the temperature of the furnace and the melting time to ensure that the raw materials can be fully melted.

[0158] In the molten iron, the composition of the molten iron is measured and then the amount of alloys of carbon, silicon, manganese, phosphorus, sulfur, copper, chromium, antimony, tin and other elements added is calculated according to the formula. These alloys are added to adjust the chemical composition of the molten iron to achieve the performance requirements of the cylinder casting.

[0159] When the temperature of the molten iron reaches more than 1400℃, sampling and analysis are carried out to ensure that the composition of the molten iron meets the predetermined standards. This step is the key to quality control and ensures that the chemical composition of the material is within a controllable range.

[0160] Before the molten iron comes out of the furnace, the temperature of the cylinder material needs to be measured again to ensure that it meets the requirements for coming out of the furnace. This step is to ensure that the material will not degrade in performance due to improper temperature during subsequent casting or processing.

[0161] After weighing each element alloy, it is necessary to reconfirm the weight of each alloy to ensure that the correct amount of alloy has been added. This step is crucial to ensure the accuracy and consistency of the material composition.

[0162] After confirming that all conditions meet the requirements, the molten iron is taken out of the furnace and prepared for the next step of casting or processing.

[0163] The molten iron after the furnace can be used to cast the cylinder block, or further heat treated and machined as needed to meet the performance requirements of the final product.

[0164] This detailed preparation method ensures the quality and performance of cylinder block castings for a wide range of high-performance engine and machinery applications. This approach emphasizes the importance of precise control of chemical composition and temperature to produce cylinder block castings that meet specific performance requirements.

[0165] Experimental Example 1

[0166] In order to further illustrate the performance of the cylinder made from the cylinder block casting of the present invention, the following experimental examples are conducted:

[0167] The method for preparing the cylinder casting comprises the following steps:

[0168] First, pig iron, steel and recycled materials are put into the furnace to heat and melt, and then the alloys of carbon, silicon, manganese, phosphorus, sulfur, copper, chromium, antimony and tin are put into the furnace for smelting, and the castings are obtained after molding.

[0169] Among them, the percentages of each element are as follows: carbon 3.2% to 3.45%, silicon 1.7% to 1.9%, manganese 0.85% to 0.9%, phosphorus 0.06% to 0.08%, sulfur 0.06% to 0.09%, copper 0.45% to 0.50%, chromium 0.17% to 0.2%, antimony 0.032% to 0.036%, and tin 0.053% to 0.058%.

[0170] When the molten iron temperature is greater than 1400°C, samples are taken to analyze the molten iron composition.

[0171] Before taking out of the furnace, measure the temperature of the cylinder material and wait until it meets the requirements before taking out of the furnace.

[0172] After weighing the weight of each element alloy, it is necessary to confirm the weight of each element alloy again.

[0173] Specifically, the cylinder block casting preparation method of the present invention is a process flow for accurately controlling the material composition and performance. The following are the specific implementation steps:

[0174] Prepare pig iron, steel and recycled materials, which are the basic raw materials for cylinder block castings.

[0175] The prepared pig iron, steel and recycled materials are put into the furnace for heating and melting. This step requires controlling the temperature of the furnace and the melting time to ensure that the raw materials can be fully melted.

[0176] In the molten iron, relevant alloys of carbon, silicon, manganese, phosphorus, sulfur, copper, chromium, antimony, tin and other elements are calculated and added according to the formula. These alloys are added to adjust the chemical composition of the molten iron to achieve the performance requirements required for the cylinder casting.

[0177] When the temperature of the molten iron reaches more than 1400℃, sampling and analysis are carried out to ensure that the composition of the molten iron meets the predetermined standards. This step is the key to quality control and ensures that the chemical composition of the material is within a controllable range.

[0178] Before the molten iron comes out of the furnace, the temperature of the cylinder material needs to be measured again to ensure that it meets the requirements for coming out of the furnace. This step is to ensure that the material will not degrade in performance due to improper temperature during subsequent casting or processing.

[0179] After weighing the alloy elements, it is necessary to re-confirm the weight of each alloy to ensure that the correct amount of alloy has been added. This step is crucial to ensure the accuracy and consistency of the material composition.

[0180] After confirming that all conditions meet the requirements, the molten iron is taken out of the furnace and prepared for the next step of casting or processing.

[0181] The molten iron after the furnace can be used to cast the cylinder block, or further heat treated and machined as needed to meet the performance requirements of the final product.

[0182] This detailed preparation method ensures the quality and performance of cylinder block castings for a wide range of high-performance engine and machinery applications. This approach emphasizes the importance of precise control of chemical composition and temperature to produce cylinder block castings that meet specific performance requirements.

[0183] The performance test of the commercial vehicle air compressor cylinder casting produced on the vertical line shows that the casting has good wear resistance, tensile strength greater than 250MPa, hardness 200-240HBW, and can reduce the high porosity defect rate of cylinder castings produced efficiently on the vertical line. The casting has excellent performance and has won praise from market customers and has good economic benefits.

[0184] Among them, the effect of the casting obtained is as follows Figures 1 to 4 As shown in the figure, it can be seen that the color of each product is smooth and the lines are prominent.

[0185] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values ​​of the parts and steps described in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.

[0186] In the description of the present application, it should be understood that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the scope of protection of the present application; the directional words "inside and outside" refer to the inside and outside relative to the contours of each component itself.

[0187] For ease of description, spatially relative terms such as "above", "above", "on the upper surface of", "above", etc. may be used here to describe the spatial positional relationship between a device or feature and other devices or features as shown in the figure. It should be understood that spatially relative terms are intended to include different orientations of the device in use or operation in addition to the orientation described in the figure. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Thus, the exemplary term "above" can include both "above" and "below". The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatially relative descriptions used here are interpreted accordingly.

[0188] In addition, it should be noted that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of this application.

[0189] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A cylinder block casting, characterized in that: The cylinder block casting includes the following elements in weight percentage: Carbon 3.2%~3.45% Silicon 1.7%~1.9% Manganese 0.85%~0.9% Phosphorus 0.06%~0.08% Sulfur 0.06%~0.09% Copper 0.45%~0.54% Chromium 0.12%~0.20% Antimony 0.026%~0.040% Tin element 0.053%~0.061%.

2. The cylinder block casting according to claim 1, characterized in that: When the cylinder block casting is single-cylinder water-cooled, the percentages of each element are as follows: Carbon 3.2%~3.45% Silicon 1.7%~1.9% Manganese 0.85%~0.9% Phosphorus 0.06%~0.08% Sulfur 0.06%~0.09% Copper 0.45%~0.50% Chromium 0.17%~0.2% Antimony 0.032%~0.036% Tin element 0.053%~0.058%.

3. The cylinder block casting according to claim 1, characterized in that: When the cylinder block casting is a double-cylinder water-cooled one, the percentages of the various elements are as follows: Carbon 3.2%~3.45% Silicon 1.7%~1.9% Manganese 0.85%~0.9% Phosphorus 0.06%~0.08% Sulfur 0.06%~0.09% Copper 0.50%~0.54% Chromium 0.17%~0.2% Antimony element 0.036%~0.040% Tin element 0.055%~0.061%.

4. The cylinder block casting according to claim 1, characterized in that: When the cylinder block casting is single-cylinder or double-cylinder air-cooled, the percentage of each element is as follows: Carbon 3.2%~3.45% Silicon 1.7%~1.9% Manganese 0.85%~0.9% Phosphorus 0.06%~0.08% Sulfur 0.06%~0.09% Copper 0.43%~0.48% Chromium 0~0.12% Antimony 0.026%~0.031% Tin element 0.053%~0.058%.

5. The cylinder block casting according to claim 1, characterized in that: The pearlite content of the cylinder block casting is greater than 98%.

6. The method for preparing a cylinder block casting according to any one of claims 1 to 5, characterized in that: The following steps are involved: First, pig iron, steel and recycled materials are put into a furnace to heat and melt. The composition of the molten iron is measured and then the amount of carbon, silicon, manganese, phosphorus, sulfur, copper, chromium, antimony and tin added to the alloy is calculated according to the formula. The alloy is put into the furnace for smelting, poured and solidified to obtain a casting.

7. The method for preparing a cylinder block casting according to claim 6, characterized in that: When the molten iron temperature is greater than 1400°C, samples are taken to analyze the molten iron composition.

8. The method for preparing a cylinder block casting according to claim 6, characterized in that: Before taking out of the furnace, measure the temperature of the cylinder material and wait until it meets the requirements before taking out of the furnace.

9. The method for preparing a cylinder block casting according to claim 6, characterized in that: After weighing the alloy of each element, it is necessary to confirm the weight of the alloy of each element again.

10. A cylinder for an automobile air compressor, characterized in that: The cylinder block casting is made by the cylinder block casting according to any one of claims 1 to 5.